The Applied Aproach Impact Information Security For Government and Company (A Review) - Febriana, Henny; Dewi Sartika Br Ginting; Fuzy Yustika Manik; Mahyuddin (Talenta Publisher, 2022)
The Government and industry are currently using information and communication technology a lot. The Government and companies in Indonesia have regulations on operational standards and management procedures for information and communication systems security at Government regarding implementing information system security. Information security is essential because there are many threats to information security. Information security in this era of Information and Communication Technology (ICT) is fundamental. Information Exchange Environment (IEE) vulnerabilities have increased as threats become more widespread and complex; therefore, information security has become a fundamental problem for businesses, organizations, and governments. So, in this paper, we will explain the review of the impact of Information Security For Government and companies in terms of threats and types of information security. Some security system methods are analyzed, among others—application Security, cloud security, Cryptography, security infrastructure, Incident response, and vulnerability management. The results of this review analysis, it known threat has several solutions, each depending on the type of threat for both the Government and the Company. Furthermore, Information Security is considered very important, especially for data stored in Government and companies.